2020
DOI: 10.3233/jad-200937
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment Is a Common Comorbidity in Deceased COVID-19 Patients: A Hospital-Based Retrospective Cohort Study

Abstract: We analyzed the frequency of cognitive impairment (CI) in deceased COVID-19 patients at a tertiary hospital in Spain. Among the 477 adult cases who died after admission from March 1 to March 31, 2020, 281 had confirmed COVID-19. CI (21.1% dementia and 8.9% mild cognitive impairment) was a common comorbidity. Subjects with CI were older, tended to live in nursing homes, had shorter time from symptom onset to death, and were rarely admitted to the ICU, receiving palliative care more often. CI is a frequent comor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 18 publications
2
22
0
3
Order By: Relevance
“…A total of 8 studies were further removed because they were not original articles, 2 studies were removed because the population was not in older adults with dementia who have COVID-19, 19 studies were removed because they didn't provide the result of the mortality, and 2 studies were removed because they didn't provide full-text article. Finally, 15 studies were included in the systematic review 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 . The selected studies are presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 8 studies were further removed because they were not original articles, 2 studies were removed because the population was not in older adults with dementia who have COVID-19, 19 studies were removed because they didn't provide the result of the mortality, and 2 studies were removed because they didn't provide full-text article. Finally, 15 studies were included in the systematic review 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 . The selected studies are presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the selected studies are summarized in Table 3 , which indicates that the included studies came from 7 different countries. Six of the studies were conducted in Italy 19 , 20 , 21 , 22 , 4 were conducted in Spain 27 , 28 , 32 , 33 , and 1 study per country was conducted in Belgium 23 , France 24 , South Korea 25 , Turkey 26 , and Japan 29 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence has suggested that AD significantly increases the morbidity of COVID-19. A retrospective study in Spain has suggested cognitive impairment (29.1%) as one of the most frequent comorbidities in deceased COVID-19 patients [63]. Moreover, AD was the most common diagnosis for cognitive impairment in the confirmed COVID-19 group (9.3% of all patients) [63].…”
Section: Ad Patients Exhibit Elevated Morbidity and Mortality Of Covid-19mentioning
confidence: 99%
“…Severe COVID-19 affects elderly with chronic diseases, including cognitive decline, in high proportion compared to general adult population [2,3]. According to recent studies, dementia is a major risk factor for COVID-19 severity [4,5]. Concomitantly, the risk of exposure to the infection is more important in patients with dementia, highly exposed in the context of long-term care facilities, frequent hospitalizations and intellectual decline.…”
Section: Introductionmentioning
confidence: 99%